PENDAMPINGAN PENYUSUNAN DOKUMEN PERIJINAN USAHA BAGI PELUKU USAHA MIKRO DAN KECIL DI KABUPATEN KEDIRI - Hidayati Nur; Saptaria Lina; Suwarsono Bambang (COMVICE: Journal Of Community Service, 2023)
Micro business actors in the Micro and Small Enterprises sector have quite an important role in national economic growth. One effort to improve the performance of Micro and Small businesses is to fulfil the legality of licensing. This is the focus of the Community Service activities carried out by the writing team. This activity is focused on assisting in preparing business licensing documents for micro and small business owners in the food and beverage sector in Purwoasri District, Kediri Regency. Documents prepared include 1) Business Identification Number, 2) Food and Beverage Home Industry Food Legal Entity, and 3) Halal Certificate up to registration via Online Single Submission (OSS). Implementing community service activities is carried out intensively for 55 fostered partners. This activity also involved the Kediri Cooperatives and Micro Enterprises Service. The program ran well and got a positive response from all parties.